PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI CANVA PADA FASE A BAB 2 AYO BERMAIN TEKS NONFIKSI “HATI-HATI” DI KELAS 1 SD NEGERI PALEBON 01 - Nafla Kapila Sumarga; Mudzanatun; Choirul Huda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The research was successfully conducted at Palebon 01 Semarang Public Elementary School that teachers experience time constraints in creating interactive, innovative, and interesting learning media, so that learning tends to use conventional methods that cause students to quickly feel bored. The type of research used is RnD with the ADDIE research model, with the aim of developing canva application learning media on phase A chapter 2 material let's play non-fiction text "Be Careful in grade 1. The results of the study indicate that the canva application learning media is feasible to use and very valid. Validation of media expert I got a percentage of 92%, media expert II a percentage of 97.3%. Validation of material expert I got a percentage of 98%, material expert II got 100%, the results of field trials provided student questionnaires showing optimal learning interest with a percentage of 97.04%. Canva-based learning media is feasible to use and can optimize student learning interest.